2020
DOI: 10.1101/2020.10.19.346064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Septate junction proteins are required for egg elongation and border cell migration during oogenesis in Drosophila

Abstract: Protein components of the invertebrate occluding junction - known as the septate junction (SJ) - are required for morphogenetic developmental events during embryogenesis in Drosophila melanogaster. In order to determine whether SJ proteins are similarly required for morphogenesis during other developmental stages, we investigated the localization and requirement of four representative SJ proteins during oogenesis: Contactin, Macroglobulin complement-related, Neurexin IV, and Coracle. A number of morphogenetic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 82 publications
(162 reference statements)
0
8
0
Order By: Relevance
“…While the phenotypes caused by Lac RNAi knockdown are mild, Lac is likely to be a true regulator of border cell migration. Recent work by Alhadyian et al found that four additional septate junction proteins, Macroglobulin complement-related (Mcr), Contactin, Neurexin-IV and Coracle, localize to border cells and are required for both border cell cluster migration and cohesion (Alhadyian et al 2021). Because border cells do not have mature septate junctions (which form the tight occluding junctions), septate junction proteins may instead regulate cluster polarity and/or adhesion during migration (Alhadyian et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…While the phenotypes caused by Lac RNAi knockdown are mild, Lac is likely to be a true regulator of border cell migration. Recent work by Alhadyian et al found that four additional septate junction proteins, Macroglobulin complement-related (Mcr), Contactin, Neurexin-IV and Coracle, localize to border cells and are required for both border cell cluster migration and cohesion (Alhadyian et al 2021). Because border cells do not have mature septate junctions (which form the tight occluding junctions), septate junction proteins may instead regulate cluster polarity and/or adhesion during migration (Alhadyian et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Core SJ proteins are localized all along the lateral membrane in stage 2–10 egg chambers, but are relocalized to an apical lateral location during stages 11 and 12. This relocalization of SJ proteins requires the presence of other SJ proteins, as RNAi against Nrx-IV or Mcr result in mislocalization of SJ proteins in stage 12 egg chambers [ 55 ]. Likewise, expression of a dominant negative Rab5 in the follicular epithelium or expression of rab11-RNAi results in mislocalized SJ proteins in stage 11/12 egg chambers.…”
Section: Biogenesis Of the Sjmentioning
confidence: 99%
“…A recent study has revealed roles for several SJ proteins in morphogenetic events that occur during oogenesis [ 55 ]. The ovaries in adult females are composed of approximately 20 ovarioles, each of which consists of linked chains of successively more developed egg chambers.…”
Section: Developmental Functions Of Sj Genesmentioning
confidence: 99%
See 2 more Smart Citations